Segmentation of CT Brain Images Using K-Means and EM Clustering - Lee, Tong Hau; Fauzi, Mohammad Faizal Ahmad; Komiya, Ryoichi (2008)
The combination of the different approaches for the segmentation of brain images is presented in this paper. The system segments the CT head images into 3 clusters, which are abnormal regions, cerebrospinal fluid (CSF) and brain matter. Firstly we filter out the abnormal regions from the intracranial area by using the decision free. As for the segmentation of the CSF and brain matter, we employed the Expectation-maximization (EM) algorithm. The system has been tested with a number of real CT head images and has achieved some promising results.